Dos problemas de sintaxis adverbial - Chuaqui Farrú, Claudia (Onomázein, 2006)
This article tackles two problems of adverbial function, e.i., adverbs as noun modifiers and the syntactic function of the adverbs más and menos in mathematical additions and substractions